Soft mechanical stimulation induces a defense response against Botrytis cinerea in strawberry - Tomas Grau, Rodrigo Hernán (2018)
Key message: Genes associated with plant mechanical stimulation were found in strawberry genome. A soft mechanical stimulation (SMS) induces molecular and biochemical changes in strawberry plants, conferring protection againstBotrytis cinerea. Abstract: Plants have the capacity to induce a defense response after exposure to abiotic stresses acquiring resistance towards pathogens. It was reported that when leaves of Arabidopsis thaliana were wounded or treated with a soft mechanical stimulation (SMS), they could resist much better the attack of the fungal pathogen Botrytis cinerea, and this effect was accompanied by an oxidative burst and the expression of touch-inducible genes (TCH). However, no further work was carried out to better characterize the induced defense response. In this paper, we report that TCH genes were identified for first time in the genomes of the strawberry species Fragaria ananassa (e.g. FaTCH2, FaTCH3, FaTCH4 and FaCML39) and Fragaria vesca (e.g. FvTCH2, FvTCH3, FvTCH4 and FvCML39). Phylogenetic studies revealed that F. ananassa TCH genes exhibited high similarity with the orthologous of F. vesca and lower with A. thaliana ones. We also present evidence that after SMS treatment on strawberry leaves, plants activate a rapid oxidative burst, callose deposition, and the up-regulation of TCH genes as well as plant defense genes such as FaPR1, FaCHI2-2, FaCAT, FaACS1 and FaOGBG-5. The latter represents the first report showing that TCH- and defense-induced genes participate in SMS-induced resistance in plants, bringing a rational explanation why plants exposed to a SMS treatment acquired an enhance resistance toward B. cinerea.